(untitled) (International Journal of Food and Nutritional Sciences, 2024)
The human diet is seeking for natural and fresh produce these days, meanwhile microgreens are a new type of food product which promotes health and longevity. Wheat Grass Microgreen (WGM) refers to the young grass of the common wheat plant (Triticum aestivum) which belong to Poaceae family. It is rich in essential nutrients therefore, the present study was conducted to determine the phytonutrients, nutritional composition, polyphenolic content and antioxidant potential in WGM and its use in food product formulation. To prepare mayonnaise, egg was substituted with WGM powder at 0, 2, 5, and 8%. The study revealed that nutrients such as carbohydrate (45.48%), protein (19.5%), crude fibre (19.88%), iron (15.2 mg) in 100 g of WGM was significantly higher. The qualitative analysis of phytochemical constituents indicated the presence of alkaloids, saponins, tannins, flavonoids, terpenoids, steroids, phenols and glycosides. The phenolic content of WGM was found highest in 100% methanol (67.33±2.30) and 90% aqueous ethanol (49.33±3.05), whereas highest flavonoid content was obtained in 90% concentration of both the methanolic (97.16±1.25) and ethanolic (103.16±2.08) solvents. Antioxidant activities of the WGM were studied through DPPH free radical scavenging activity, ferric reducing antioxidant power, and metal chelating activity. The result indicates that 50% methanol was more effective for extraction of bioactive compounds because the highest DPPH activity (39.57±1.66), FRAP activity (9.26±0.05) and Metal chelating activity (56.80±1.70) were obtained in 50% methanol. Of all the treatments, W3 treatment was most acceptable on the basis of overall sensory score of 8.33 and t-test. In conclusion, the WGM powder contains several crucial nutrients such as iron whose incorporation would subsequently, providing a distinct flavour and boost the nutritional aspects of the developed product specially in anaemia. Additionally, good polyphenolic and antioxidant value depicts that it contains several secondary metabolites which could be used to reduce oxidative stress and related health conditions.